An improvement in DEA cross‐efficiency aggregation based on the Shannon entropy. (8th November 2016) - Song, Lianlian; Liu, Fan
Abstract: This paper improves a recently proposed Data Envelopment Analysis (DEA) cross‐efficiency aggregation method based on the Shannon entropy. The weights for determining cross‐efficiency are derived from minimizing the square distance of weighted cross‐efficiency and weighted CCR efficiency. Our calculation example indicates that this method may produce inappropriate weights, which is significantly inconsistent with a widely accepted viewpoint. A variance coefficient method based on the Shannon entropy is presented to overcome the drawbacks of the DEA cross‐efficiency aggregation method. In this study, comparisons of weights and cross‐efficiency scores are provided.